CN10Cancer care through the fire and flames: 3-year experience in the utilisation of electronic consultation and referral system at the red zone in Southern Thailand. (1st October 2019) - Rattanakhot, N; Dechaphunkul, A; Sunpaweravong, P; Sathitruangsak, C; Maisrikrod, A; Songserm, M; Jiratrachu, R; Sangthawan, D; Peerawong, T; Phungrassami, T; Rordlamool, P; Sakdejayont, S
Abstract: Background: "The South Thailand Insurgency" is burning violence in the deep south of Thailand. The insurgency which has been ongoing since 2004 has played out in the three southern most districts of the country Pattani, Yala and Narathiwat and some area of Songkhla, so-called the "Red Zone". Violence such as daily ambush, bombing on soldiers and civilians, caused people living in terror. This violence has affected cancer service. Many cancer patients gave up on their lives due to struggle with the disease itself, security concerns, traveling and caregiving burden led to a high loss to follow-up rate. We, an oncology service team working at Songklanagarind hospital, the only one radiation and oncology center located in this area, in cooperation with doctors and nurses working in the Red Zone created a network and utilized an electronic consultation and referral system to alleviate these suffering. We preliminarily reported its real-life performance in 3 years period. Methods: Electronic consultation system(E-consult) was a web-based program designed and developed to provide advice and facilitate the referral process in cancer care. Since October 2015, we prospectively surveyed the impact of this pilot project on the quality of service by counting waiting time, the number of center visit until treatment, unnecessary referral avoidance, patient and potential cost saving compared to the normal referral system. Results: E-consult reached out to 7 hospitals and 589 patient referred through E-consult. Among patients from the Red Zone, without E-consult, their average waiting time was 56.4 days, the number of visits was 6.5 visits. The estimated financial burden was 758.8 per patient. After the implementation of E-consult in 259 patients, the average time to treatment was 41.5 days (p = 0.006) and the number of counter visit was 2.3 visits (p < 0.001). The estimated financial burden was 358.7(p < 0.001). We prevented 28 patients from the unnecessary referral. Conclusions: In this special context, the electronic referral system not only was helpful to improve medical access, timeliness to specialist care, saving the patients' family time and resources but it also supports the doctors and nurses on duty in the Red Zone. Legal entity responsible for the study: Nanthiya Rattanakhot. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.